PROSPECTS FOR THE USE OF VACUUM CAPTURE DEVICESIN LIGHT INDUSTRY - ROMANETS, TARAS; NEIMAK, VITALII; MAIDAN, PAVLO; SMUTKO, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work concerns the automation of technological processes in light industry. In particular, the possibility of equipping industrial robots and manipulators with pumpless vacuum gripping devices of the vacuum type is being considered. The existing technical solutions of vacuum gripping devices for flat objects of low rigidity and complex shape are analyzed. The dependences of the change in the volume of the vacuum chamber of the pumpless gripper during the manipulation process, which are necessary for calculating the structural parameters of the working bodies of these grippers and for determining the technological modes of their operation, have been obtained. Also, the indicated dependencies can be used in the analytical description of the process of air inflow into the chamber of a pumpless vacuum gripper to determine the dependence of the time of air inflow into the vacuum chamber on the structural and technological parameters of the gripping device, as well as on the physical and mechanical properties of the manipulation object. This will make it possible to design pumpless vacuum gripping devices for handling parts of the shoe industry, and will also be useful in choosing the modes of operation of gripping devices of this type.